2013
DOI: 10.1155/2013/129723
|View full text |Cite
|
Sign up to set email alerts
|

Early Therapeutic Drug Monitoring for Isoniazid and Rifampin among Diabetics with Newly Diagnosed Tuberculosis in Virginia, USA

Abstract: Slow responders to tuberculosis (TB) treatment in Virginia have prolonged treatment duration and consume more programmatic resources. Diabetes is an independent risk factor for slow response and low serum anti-TB drug concentrations. Thus, a statewide initiative of early therapeutic drug monitoring (TDM) for isoniazid and rifampin at 2 weeks after TB treatment was piloted for all diabetics with newly diagnosed TB. During the period of early TDM, 12/01/2011–12/31/2012, 21 diabetics had C 2 hr concentrations per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 20 publications
1
28
0
Order By: Relevance
“…A near inverse correlation was obtained in diabetic patients (Pearson's correlation=-0.402, P value=0.001); however such a correlation was not observed in non-diabetic pulmonary tuberculosis patients suggesting that the drug absorption is disfavoured only under hyperglycemic conditions and linear relationship does not exist between blood glucose and rifampicin Cmax (Pearson's correlation=0.006, P Value=0.962). This is similar to the study reported by Nijland et al (2006), Heysell et al (2010) and Heysell et al (2013) [12,[16][17]. The RBS vs Cmax correlation plot of non-diabetic and diabetic PTB patients is shown in fig.…”
Section: Fig 2: Distribution Based On Cat Regimensupporting
confidence: 90%
See 1 more Smart Citation
“…A near inverse correlation was obtained in diabetic patients (Pearson's correlation=-0.402, P value=0.001); however such a correlation was not observed in non-diabetic pulmonary tuberculosis patients suggesting that the drug absorption is disfavoured only under hyperglycemic conditions and linear relationship does not exist between blood glucose and rifampicin Cmax (Pearson's correlation=0.006, P Value=0.962). This is similar to the study reported by Nijland et al (2006), Heysell et al (2010) and Heysell et al (2013) [12,[16][17]. The RBS vs Cmax correlation plot of non-diabetic and diabetic PTB patients is shown in fig.…”
Section: Fig 2: Distribution Based On Cat Regimensupporting
confidence: 90%
“…Being highly pH dependent for solubility and well absorbed from an acidic pH, a shift in the gastric pH due to hyperglycemia delays rifampicin absorption and thereby tend to prolong the tmax and decrease the Cmax [15]. In addition, gastrointestinal ailments such as gastroparesis which are common in chronic diabetics may either delay or impair absorption of rifampicin leading to decreased systemic availability [17]. Univariate analyses were performed to determine the relationship between random blood glucose and rifampicin Cmax.…”
Section: Fig 2: Distribution Based On Cat Regimenmentioning
confidence: 99%
“…TDM has been shown to be beneficial in the treatment of TB (14)(15)(16)(17)(18)(19). Additionally, several studies have shown that TB drug concentrations lower than the expected range are a risk factor for treatment failure (20)(21)(22)(23).…”
mentioning
confidence: 99%
“…A standard low-fat diet was provided 3, 6, and 12 h after medication intake; the patients were allowed to ingest water ad libitum (17,18). After the drugs were administered, blood samples were collected 0.33, 0.66, 1, 1.5, 2, 2.5, 3,4,6,8,12, and 24 h postdose. Plasma was immediately separated and frozen at Ϫ80°C prior to analysis.…”
Section: Methodsmentioning
confidence: 99%
“…T2DM was associated with more-severe clinical manifestations (adjusted odds ratio [OR] ϭ 1.80), delayed sputum conversion (OR ϭ 1.51), and a higher probability of treatment failure (OR ϭ 2.93) (9). Differences in the pharmacokinetics (PK) of rifampin (RIF), the most important anti-TB concentration-dependent drug, may contribute to an increased risk of TB treatment failure for diabetic patients (10)(11)(12)(13)(14). Additionally, the study by Jiménez-Corona et al showed that TB recurrence in diabetic individuals compared with nondiabetic individuals was caused by MTC of the same genotype in 81% of cases, indicating a predominance of relapse over exogenous reinfection (9).…”
mentioning
confidence: 99%